Extended-Spectrum Beta-Lactamase-Producing Escherichia coli in Drinking Water Samples From a Forcibly Displaced, Densely Populated Community Setting in Bangladesh - Mahmud, Zahid Hayat; Kabir, Mir Himayet; Ali, Sobur; Moniruzzaman, M.; Imran, Khan Mohammad; Nafiz, Tanvir Noor; Islam, Md. Shafiqul; Hussain, Arif; Hakim, Syed Adnan Ibna; Worth, Martin; Ahmed, Dilruba; Johnston, Dara; et al. (Frontiers in Public Health, 2020)
Introduction: Community-acquired infections due to extended-spectrum beta-lactamase (ESBL) producing Escherichia coli are rising worldwide, resulting in increased morbidity, mortality, and healthcare costs, especially where poor sanitation and inadequate hygienic practices are very common. Objective: This study was conducted to investigate the prevalence and characterization of multidrug-resistant (MDR) and ESBL-producing E. coli in drinking water samples collected from Rohingya camps, Bangladesh. Methods: A total of 384 E. coli isolates were analyzed in this study, of which 203 were from household or point-of-use (POU) water samples, and 181 were from source water samples. The isolates were tested for virulence genes, ESBL-producing genes, antimicrobial susceptibility by VITEK 2 assay, plasmid profiling, and conjugal transfer of AMR genes. Results: Of the 384 E. coli isolates tested, 17% (n = 66/384) were found to be ESBL producers. The abundance of ESBL-producers in source water contaminated with E. coli was observed to be 14% (27/181), whereas, 19% (39/203) ESBL producers was found in for household POU water samples contaminated with E. coli, it was 18% (37/203). We detected 71% (47/ out of 66) ESBL-E. coli to be MDR (71.2 %). Among these 47 MDR isolates, 20 were resistant to three classes, and 27 were resistant to four different classes of antibiotics. Sixty-four three percent (42/66) of the ESBL producing E. coli isolates carried 1 to 7 several plasmids ranging from 1 to 103 MDa. Only large plasmids with antibiotic resistance properties were found transferrable via conjugation. Moreover, around 7% (29/384) of E. coli isolates harbored at least one of 10 virulence factors belonging to different E. coli pathotypes. Conclusions: The findings of this study suggest that the drinking water samples analyzed herein could serve as an important source for exposure and dissemination of MDR, ESBL-producing and pathogenic E. coli lineages, which therewith pose a health risk to the displaced Rohingya people residing in the densely populated camps of Bangladesh.